2016
DOI: 10.1021/acs.jpcc.6b05186
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Intermixed Oxide Surfaces: Fe, Ni, Cr, and V Oxides on Rutile TiO2(011)

Abstract: The oxide/oxide interface for monolayer oxides on rutile TiO 2 (011) substrates is investigated for several transition metal (M) oxides, with M= Fe, Ni, Cr, and V. The samples are prepared using ultra-high vacuum sample preparation procedures and are characterized with a combination of photoemission spectroscopy and scanning tunneling microscopy (STM). Furthermore, stable intermixed monolayer oxides are determined by density functional theory (DFT) based simulations and compared to the experimental results. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A pseudohexagonal structure that somehow resembles the one in Figure a has been observed in ref . Such a structure was attributed to Ca impurities segregating from crystal bulk or intentionally prepared as mixed oxide monolayer by depositing metals (Fe, Cr, Ni, V) in oxidizing atmosphere . In order to address the possible presence of such impurities, we complemented the XPS measurements with LEISa method that provides an extremely high sensitivity to the composition of the topmost atomic layer.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…A pseudohexagonal structure that somehow resembles the one in Figure a has been observed in ref . Such a structure was attributed to Ca impurities segregating from crystal bulk or intentionally prepared as mixed oxide monolayer by depositing metals (Fe, Cr, Ni, V) in oxidizing atmosphere . In order to address the possible presence of such impurities, we complemented the XPS measurements with LEISa method that provides an extremely high sensitivity to the composition of the topmost atomic layer.…”
Section: Resultsmentioning
confidence: 76%
“…Such a structure was attributed to Ca impurities segregating from crystal bulk 30 or intentionally prepared as mixed oxide monolayer by depositing metals (Fe, Cr, Ni, V) in oxidizing atmosphere. 31 In order to address the possible presence of such impurities, we complemented the XPS measurements with LEIS—a method that provides an extremely high sensitivity to the composition of the topmost atomic layer. On the UHV-prepared surface only the O (mass 16) and Ti (mass 48) peaks were detected (see Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed scan spectrum of Ti 2p is presented in Figure 10c and composed of two components. The characteristic of peaks 5 (464.24 eV) and 4 (458.19 eV) was obviously attributed to the XPS spectrum of Ti 2p in rutile bulk [8,31,32]. Combined with the previous analysis, peak 4 (458.84 eV) and peak 7 (461.19 eV) were tentatively assigned to the Ti 4+ states in Ti-OH and Ti-O-Bi 2+ on the surface of rutile.…”
Section: Xps Analysismentioning
confidence: 62%
“…Under controlled UHV preparation conditions these metal atoms intermix with the atoms in the surface of the substrate and form mixed oxide monolayers. 8 Interestingly, we observed that the transition metals selected in our study formed an universal structure on the TiO 2 (011) surface that based on DFT simulations was identified to exhibit a MTi 2 O 5 composition for all M investigated, i.e., M = Fe, V, Ni, and Cr. There are two main aspects that motivate the study of monolayer oxides on bulk oxide substrates in the field of chemical surface properties: (i) All technological materials possess some bulk impurities (sometimes bulk dopants, including iron, are added on purpose), and these impurities/ dopants may under certain thermodynamic conditions segregate to the surface.…”
Section: Introductionmentioning
confidence: 51%